ANALISIS KUALITAS PELAYANAN BANQUET SECTION TERHADAP KEPUASAN TAMU THE WUJIL RESORT AND CONVENTION UNGARAN - Ndaru Prasastono; Ema Rahmawati; Sri Yulianto Fajar Pradapa (Pringgitan, 2020)
The aim of this research is to find out and analyze the quality of the service banquet section on the satisfaction of guests of The Wujil Resort and Convention Ungaran. The method used in this research is descriptive, with the respondent being a company or agency carrying out activities or events at The Wujil Resort and Convention Ungaran with a total of 50 representatives of these companies or agencies. Data collection techniques used were observation, guest commentary and literature study. The quality of service is influenced by five dimensions, namely reliability, responsiveness, assurance, empathy and physical evidence. While the satisfaction of guests or customers is also influenced by five dimensions: staying loyal, buying the product offered, recommending the product, being willing to pay more, and giving input. From the results of data analysis shows that respondents stated both the Banquet Section service quality and expressed agreement or satisfaction with guest or customer satisfaction.Keywords: Service Quality, Banquet Section and Guest Satisfaction